2010
DOI: 10.1002/gepi.20528
|View full text |Cite
|
Sign up to set email alerts
|

Testing for non‐random mating: evidence for ancestry‐related assortative mating in the Framingham heart study

Abstract: Population stratification leads to a predictable phenomenon—a reduction in the number of heterozygotes compared to that calculated assuming Hardy-Weinberg Equilibrium (HWE). We show that population stratification results in another phenomenon—an excess in the proportion of spouse-pairs with the same genotypes at all ancestrally informative markers, resulting in ancestrally related positive assortative mating. We use principal components analysis to show that there is evidence of population stratification withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
49
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 14 publications
5
49
0
Order By: Relevance
“…Recent work from several groups suggests that genetic factors contribute to human mating preferences (5,(7)(8)(9)(10). In European populations, there is evidence that individuals tend to be attracted to people with major histocompatibility complex (MHC) regions that are distinct from their own (7,8).…”
mentioning
confidence: 99%
“…Recent work from several groups suggests that genetic factors contribute to human mating preferences (5,(7)(8)(9)(10). In European populations, there is evidence that individuals tend to be attracted to people with major histocompatibility complex (MHC) regions that are distinct from their own (7,8).…”
mentioning
confidence: 99%
“…Some studies have indicated that there is ancestrally related positive assortative mating in the FHS. 17 Fortunately, our method is neither influenced by assortative mating nor by non-random mating, a major advantage clearly demonstrated in our simulation. There are three groups of the FHS participants, the original cohort, the offspring cohort and the third generation cohort, which consist of 5209, 5124 and 4095 participants, respectively.…”
Section: Application To Fhs Datamentioning
confidence: 67%
“…Estimates of the number of generations since admixture in the Mexican population (Johnson et al 2011) range from 10 to 15, so it is reasonable to assume that equilibrium on the X chromosome for males and females should have been reached in the Mexican population if mating in this population is completely at random. Previous studies (Risch et al 2009;Sebro et al 2010), however, have shown evidence of nonrandom mating in Mexican populations. In the HapMap MXL, we detected significant evidence of assortative mating among mate pairs that produced an offspring, where the correlation of European and Native American ancestries on both the autosomes and the X chromosome is significantly higher for mate pairs than what would be expected under the null hypothesis of a random mating population.…”
Section: Discussionmentioning
confidence: 83%